Economic Actors and Liberal Dependent Capitalism - Bluhm, Katharina (Journal of Economic Sociology, 2015)
Dr. Prof. Katharina Bluhm, head of the Institute for East European Studies at Free University of Berlin, was interviewed by Zoya Kotelnikova, assistant professor and senior research fellow at the National Research University Higher School of Economics in July 2014. In this conversation, Prof. Bluhm talked about the recently published book Business Leaders and New Varieties of Capitalism in Post-Communist Europe which she edited together with Bernd Martens and Vera Trappmann. The book includes sections by the editors as well as by György Lengyel, Béla Janky, Krzysztof Jasiecki, and others. The book presents results from an international survey of entrepreneurs and top managers in East Germany, West Germany, Hungary, and Poland. The book begins with the notion that we should bring back economic actors, with their cultural ideas on what capitalism should be, into the core of the literature on varieties of capitalism in Europe. An approach centered on economic actors appears most attractive to the authors, who attempt to explain the convergence of ideas about the social role of companies and trade unions, in order to better understand the models of capitalism emerging in Central and Eastern European countries. Finally, the interview includes a discussion of liberal dependent capitalism and attitudes to multinational economic elites in post-communist Europe.